Comparação do efeito placebo entre dispositivos de acupuntura não penetrantes e acupuntura real em individuos saudáveis: estudo clínico aleatório - Maciel, Leonardo Yung dos Santos (2016)
Introduction: Several studies have used sham acupuncture methods in recent years as a way of masking to test the real effect of real acupuncture, however the placebo method selection has not followed methodological criteria to create a consensus on what the best option to use. This study aimed to evaluate the effectiveness of three placebo acupuncture methods for masking applied in healthy subjects and observe the effect of the types of placebo and real acupuncture in the skin and deep sensitivity threshold. Methods: 321 healthy volunteers were randomly divided into seven groups using the ST25 point (abdominal) to puncture, and seven groups using the BL52 point (lumbar), real acupuncture was applied and three different methods of placebo acupuncture, It was also mixed real acupuncture and sham acupuncture in the same person, totaling fourteen groups, evaluations of skin and deep sensitivity and the questionnaire were performed before and immediately after applying the technique by the investigator who was unaware of the technique had been applied. Results: The question that asked if the volunteer believed received real acupuncture or placebo showed no significant result, the percentage of subjects who reported believe that having received real acupuncture in the ST25 point was 69.56% in real group, 86.95% group Park Sham, 82.60% needle + foam, 91.30% insertion and removal, 78.26% real + Park Sham, 86.36% + real needle and foam and 86.95% + real insertion and removal and at the point BL52 was 86.36% in real group, 86.95% group Park Sham, 69.56% needle + foam, 72% insertion and removal, 86.95% real + Park Sham, 81.81% real and needle + foam and 78.26% real + insertion and removal. The skin sensitivity threshold showed no statistical difference in the intragroup analysis and in the comparison between groups, the pressure pain threshold showed a decrease in the value after the technique of application only at the real group BL52 (p = 0.044) and insert and removal BL52 (p = 0.037) for intragroup analysis and showed a statistical difference between groups real group ST25 compared with Park Sham BL52 (p <0.05) and Real in BL52 compared with insertion and removal at the point BL52 (p <0.05). Conclusion: placebo acupuncture groups used are effective in masking acupuncture research, and none of the placebo methods demonstrated have greater advantage for use in clinical trials. The skin sensitivity threshold remains unchanged after applying acupuncture or placebo, but these techniques influence the pressure pain threshold.